Dinamika Penerapan Fiqh Siyasah Dalam Mewujudkan Keadilan Dan Kesejahteraan Umat Di Tengah Tantangan Modern - Adinda Salsa Sabillah (Albayan Journal of Islam and Muslim Societies, 2025)
Fiqh siyasah is a branch of Islamic law that plays an important role in regulating governance and social life to achieve justice and public welfare. In the modern era, the implementation of fiqh siyasah faces various challenges arising from technological advancements, globalization, democracy, human rights issues, and increasingly complex social changes. This study aims to examine the dynamics of implementing fiqh siyasah in realizing justice and public welfare and to assess its relevance in addressing the needs of contemporary society. The method used is a library research approach with a descriptive qualitative analysis of various literature related to fiqh siyasah and governance. The findings indicate that the core principles of fiqh siyasah, such as justice, consultation (shura), trustworthiness, transparency, and public benefit (maslahah), remain highly relevant in modern governance systems. The application of these principles can support the establishment of good governance, improve public welfare, and maintain social and political stability. However, continuous ijtihad and adaptation to contemporary developments are necessary to ensure that fiqh siyasah remains capable of addressing modern challenges without neglecting the fundamental values of Islamic law. Therefore, fiqh siyasah can serve as an effective foundation for building a just, inclusive, and welfare-oriented government amid the evolving challenges of the modern world.